Hybrid Methods of Cipher-text and RSA Cryptographic Algorithm Using Classical Vigenère - Siska Anraeni; Herdianti Herdianti; Mursyid Mursyid (International Journal of Computing and Informatics (IJCANDI), 2016)
Maintaining the security of messages is a very important thing both within an organization and the personal especially in the age of information technology today. In order to the sent message does not fall into the one’s hands who are not interested, then encryption should be created to maintain the confidentiality of a message remains secure. Classical cryptography method using Vigenère Cipher and RSA (Riverst Shamir Adleman) is one of securing methods which will be used. In this case, the initial process is doing encryption on Vigenère cipher that produces a temporary ciphertext. The temporary ciphertext will be a plaintext on the RSA algorithm and then encrypted again to produce the actual ciphertext. Merging these two methods produces a ciphertext that is more powerful and difficult to solve.